Creeping Revolution: Avant-Garde Transfers in Central Europe (as Exemplified by Postwar Surrealism) - Orska, Joanna (Porównania, 2023)
This entry approaches the issue of avant-garde transfers in Central Europe’s literature during the twentieth and twenty-first centuries; the surrealist’s programme and phenomena being the matter of research. Despite the geographic proximity before and after WW II, avant-garde traditions developed in this area in a relative separation. The avant-garde transfers were conditioned firstly by the dominant cultural centres before the WW II. Later, the deciding impact was carried out by different political-cultural strategies of communism, including censorship issues. The comparative area consists of Czechoslovakia with the strong although dissident surrealist tradition; Slovenia as part of Tito’s Yugoslavia with its surrealist neo-avantgarde input; and Poland where legitimate surrealism never existed. This choice was made because of the considerable transfer of the surrealism-driven poetry of these countries in Poland after 1989.